The Cost of Anesthesia Drugs Workshop - James Ibinson; David G. Metro (Association of American Medical Colleges, 2012)
Abstract Introduction While trainees are often introduced to a variety of drugs and anesthetic techniques, it is not typically accompanied by an informed discussion regarding their financial costs. As a result, many academic practitioners are unaware of the actual cost of medications, and rely on opinions or historical reasoning for their information. As health care continues to evolve, costs will become more important not only to private practitioners who incur these costs, but to everyone involved in the provision of health care. This resource is a small step towards building awareness of this area. Methods The purpose of this 1.5-hour long workshop is to introduce attendees to the costs associated with anesthetic drugs so they will be able to compare different techniques. The workshop contains a PowerPoint presentation, followed by a small-group discussion where different groups are asked to create anesthetic plans and determine costs for an inhalational anesthetic, a total intravenous anesthetic, or a regional anesthetic with sedation. This is then followed by a large-group discussion where the small groups present their findings, before concluding with a PowerPoint presentation and the distribution of a reference handout. Results This workshop has been successfully deployed as part of our annual resident lecture didactic series. Discussion Many residents and practicing anesthesiologists are unaware of the costs of the anesthetic agents that they use each day. This workshop is useful way to introduce this topic.